Sustainability of pension schemes:building a smooth automatic balance mechanism with an application to the us social security - Gannon, Frederic; Legros, Florence; Touzé, Vincent (Paris, 2016)
"We build a "smooth" automatic balance mechanism (S–ABM) which would result from an optimal tradeoff between increasing the receipts and reducing the pension expenditures. The S-ABM obtains from minimizing an intertemporal discounted quadratic loss function under an intertemporal budget balance constraint. The main advantage of our model of "optimal" adjustment is its ability to analyse various configurations in terms of automatic balance mechanisms (ABM) by controlling the adjustment pace. This S-ABM permits to identify two limit cases: the “flat Swedish-type ABM” and the “fiscal-cliff US- type ABM”. These cases are obtained by assuming very high adjustment costs on revenue (implying only pension benefit adjustment) and by choosing particular sequences of public discount rates. We then apply this ABM to the case of the United States Social Security to evaluate the adjustments necessary to ensure financial solvency. These assessments are made under various assumptions about forecast time horizon, public discount factor and weighting of social costs associated with increased receipts or lower expenditures."